Effect of various decontamination procedures on disposable N95 mask integrity and SARS-CoV-2 infectivity. Issue 1 (11th June 2020) - Smith, Jeffrey S.; Hanseler, Haley; Welle, John; Rattray, Rogan; Campbell, Mary; Brotherton, Tacy; Moudgil, Tarsem; Pack, Thomas F.; Wegmann, Keith; Jensen, Shawn; Jin, Justin; Bifulco, Carlo B.; et al.
Abstract: Introduction: The COVID-19 pandemic has created a high demand on personal protective equipment, including disposable N95 masks. Given the need for mask reuse, we tested the feasibility of vaporized hydrogen peroxide (VHP), ultraviolet light (UV), and ethanol decontamination strategies on N95 mask integrity and the ability to remove the infectious potential of SARS-CoV-2. Methods: Disposable N95 masks, including medical grade (1860, 1870+) and industrial grade (8511) masks, were treated by VHP, UV, and ethanol decontamination. Mask degradation was tested using a quantitative respirator fit testing. Pooled clinical samples of SARS-CoV-2 were applied to mask samples, treated, and then either sent immediately for real-time reverse transcriptase–polymerase chain reaction (RT-PCR) or incubated with Vero E6 cells to assess for virucidal effect. Results: Both ethanol and UV decontamination showed functional degradation to different degrees while VHP treatment showed no significant change after two treatments. We also report a single SARS-CoV-2 virucidal experiment using Vero E6 cell infection in which only ethanol treatment eliminated detectable SARS-CoV-2 RNA. Conclusions: We hope our data will guide further research for evidenced-based decisions for disposable N95 mask reuse and help protect caregivers from SARS-CoV-2 and other pathogens.